PLANETARY HEALTH IN THE AMAZON: IMPACTS OF CLIMATE CHANGE AND MULTIPROFESSIONAL RESPONSES TO GLOBAL HEALTH CHALLENGES - Coelho, Patrícia dos Santos Moutinho; de Sales, Mariana Elizabeth Lopes; Brilhante, Vânia Cristina Ribeiro; dos Santos, Adriana Almeida; de Sousa, Leidiane Braz; Correa, Amanda Emanuele dos Santos; Pires, Patrícia Gabrielly da Silva; de Morais Filho, Valdemar Mendes; Cardoso, Leidson Frank Santana; de Lima, Priscila Bezerra; de Araújo, Kátia Lamara; Lopes, Jander Marcus Cirino; et al. (Seven Editora, 2026)
Climate change represents one of the greatest contemporary challenges to global health, directly affecting environmental, social, and epidemiological dynamics in various regions of the planet. The Amazon stands out in this scenario due to its ecological relevance and its influence on the global climate balance. This chapter aims to analyze the impacts of climate change in the Amazon and to discuss the role of multiprofessional teams in building integrated responses to global health challenges. This is a qualitative study, developed through an integrative review of the scientific literature, with searches conducted in international databases such as PubMed, Scopus, Web of Science, SciELO, and the Virtual Health Library, including publications from 2016 to 2025. The results show that phenomena such as deforestation, wildfires, and air pollution have contributed to an increase in respiratory, cardiovascular, and infectious diseases, in addition to expanding social vulnerabilities among indigenous and riverside communities. In this context, the importance of multiprofessional action is highlighted, involving physicians, nurses, pharmacists, physiotherapists, nutritionists, dentists, and public health professionals in epidemiological surveillance, health promotion, and the implementation of comprehensive care strategies. It is concluded that the preservation of the Amazon and the integration between environmental and health policies are essential to address the challenges of planetary health, strengthen resilient health systems, and promote better living conditions for current and future populations.